Modelling Thoracolumbar Fractures in Goat Vertebrae Based on Axial Compression Force - Febrian, Firas; Airlangga, Primadenny Ariesa; Hernugrahanto, Kukuh Dwiputra (Scripta Medica, 2024)
Background/Aim: A profound understanding of the biomechanics underlying thoracolumbar animal models has become important in spine research. Aim of this study was to analyse difference in thoracolumbar fractures based on height loss caused by axial compression force. Methods: This in vitro study used a randomised post-test only control group design. This study used goat vertebrae to make thoracolumbar fracture models based on axial compression force. Samples were divided into three groups on a single vertebral body and three groups on a single function spinal unit (FSU). Axial compression force was applied to vertebrae and FSU, reducing height by 20 %, 40 % and 60 % in different test groups.Results: This study showed that the crushing pressure in one vertebra was approximately 4565.76 ± 722.93 Pa, and in one FSU, it was approximately 5070.4 ± 703.74 Pa. Different fractures were seen based on height loss. In the 20 % loss group, nine types of wedge fractures were found. In the 40 % loss group, two types of wedge fractures and seven incomplete burst fractures were observed. The 60 % loss group had nine types of complete burst fractures in single corpus testing, two incomplete burst fractures and seven complete burst fractures in single FSU testing.Conclusion: There were differences in fracture configurations in goat vertebrae based on the height loss due to compression force in the single corpus and FSU.